Pelatihan Penggunaan Pronomina Pada Anak-Anak dalam Menulis Cerita Pendek di Gampong Jeumpa - Nofiana S; Nurjannah; Rahmi, Hayatun (Yayasan Sagita Akademia Maju, 2024)
The definition of a pronoun is a pronoun that replaces a noun or noun phrase. Examples are me, his, this. Based on the text quote, the first sentence reads: Every parent will love their child. Then, in the next sentence the word parents is no longer mentioned and is changed to use the pronoun itself, namely me. Writing I is used as a parental pronoun. Pronouns are also called pronouns. This means all words that are used to replace nouns or words that are used as objects. training on the use of pronouns for children in Gampong Jeumpa in writing short stories so that the pronouns used are not monotonous. The method used in this community service is by using lectures, questions and answers, and group work under direct guidance. This community service activity proved successful after they received the material and were guided and guided directly by lecturers and students so that in the end they were able to use various pronouns in writing short stories so that they were not monotonous in telling stories. Overall, this community service activity ran smoothly, where there were other supporting factors such as activities that were carried out in accordance with the objectives and on target.